Representing Angst and Authenticity: A Sartrean Study of Existential Crisis in Lala Bohang’s Trilogy - Raisha Srikandi Sekartaji; Ice Sariyati; Agry Pramita (Lembaga Teewan Journal Solutions, 2026)
This study examines the representation of existential crisis in Lala Bohang’s trilogy The Book of Forbidden Feelings (2016), The Book of Invisible Questions (2017), and The Book of Imaginary Beliefs (2019). Bohang’s trilogy presents fragmented reflections that portray an individual’s confrontation with freedom, uncertainty, and the burden of personal choice. This research aims to analyze how Sartrean concepts of angst and authenticity are represented in Bohang’s works. Using a qualitative descriptive method, the study applies Jean-Paul Sartre’s existentialist framework, focusing on the concepts of angst, authenticity, and bad faith. The analysis is conducted on selected textual excerpts that depict the subject’s responses to existential pressure and social expectations. The findings reveal that existential angst emerges from the subject’s awareness of radical freedom and the inevitability of choice. Authenticity is reflected when the subject acknowledges this freedom and accepts responsibility for their decisions without seeking external justification. However, certain moments also suggest the possibility of bad faith when responsibility is displaced onto circumstances or external forces. In conclusion, Bohang’s trilogy illustrates the dynamic tension between angst and authenticity, showing how individuals negotiate freedom and responsibility in their search for meaning.